Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dealer Astra Motor Honda M. Yamin Samarinda - Sarah Sasca Hisana; Irsan Tricahyadinata; Purwinahyu Purwinahyu (Indo Publishing, 2026)
This study aims to analyze the influence of organizational culture and transformational leadership style on employee performance at Astra Motor Honda M. Yamin Samarinda Dealer. The research uses a quantitative approach with a population of 78 employees, using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that organizational culture does not have a significant effect on employee performance. Meanwhile, transformational leadership style has a positive and significant effect on employee performance. This indicates that leadership plays a more dominant role in improving employee performance compared to organizational culture. This study is expected to provide useful input for management in improving employee performance and developing effective human resource management strategies.